Analysis of Harmonics and Ripple Current in Multi-module Converters with Increasing Number of Modules for High Power Applications - D. Venkatasubramanian; S. P. Natarajan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
Controlled rectifiers are considered as the most important hardware part in the field of HVDC systems in transmission lines and can be used for a number of power electronics based system operation, control and utility applications. In this paper, a brief design of a 12-pulse, 24-pulse, 36-pulse and a 48-pulse converter connected to the grid is presented along with the harmonic and ripple current analysis with its comparison statistics and thus providing a justification for the suitable ones. The performance of the 12, 24, 36 and 48-pulse converters are compared for their effectiveness in both quantitatively as well as qualitatively. Further, comparison of the 48-pulse converter on its THD and current ripple which is connected towards the grid with simple pulse width modulation technique is also proposed. It combines all features of the low switching concepts and DC current re-injection techniques. Some basic topological explanation of the controlled rectifiers and simulation results using MATLAB are also presented in this paper in order to justify the harmonic analysis. The simulation results along with the quantitative results shows the effectiveness of the proposed scheme for the cancelation or the elimination of the harmonics result in maximum harmonic mitigation, for high power utility applications, the 48-pulse converter is most fitting to improve the conversion efficiency, low di/dt and dv/dtand active and reactive power controllability.